FORMULASI STRATEGI BERSAING DI KAFE DAN ANGKRINGAN NU LAHARJO MOJOKERTO - Zenita Afifah Fitriyani; Mokhammad Ridha; Sugeng Eko Yuli Waluyo (Universitas Muhammadiyah Gresik, 2021)
ABSTRACT The purpose of this study was to identify a SWOT analysis and formulate a business strategy using the IFE and EFE matrix, as well as the Grand Strategy matrix at the Café and Angkringan Nu Laharjo Mojokerto. The benefits of the research are identified SWOT analysis and strategy formulation can be used as a measure in future business planning. The research used is qualitative research, while the data analysis technique uses descriptive analysis, namely describing the data collected using SWOT analysis, IFE and EFE matrix, and the Grand Strategy matrix. The results show that the SWOT analysis is identified, the IFE and EFE matrices have a positive total score, and the Grand Strategy matrix shows that Nu Laharjo Café and Angkringan are in a strategic and good position. Keywords : Strategy Formulation, SWOT Analysis, IFE and EFE Matrix, Grand Strategy Matrix